Energy Storage Systems: Tracking the Influence of Thermal Expansion and Oxygen Vacancies on the Thermal Stability of Ni‐Rich Layered Cathode Materials (Adv. Sci. 12/2020). Issue 12 (24th June 2020) - Lee, Eunkang; Muhammad, Shoaib; Kim, Taewhan; Kim, Hyunchul; Lee, Wontae; Yoon, Won‐Sub
Abstract : Close relationship between Ni content and inherent thermal instability of Ni‐rich cathode material has been widely investigated. However, the underlying cause of thermal instability of Ni‐rich cathode material involving Ni has not been fully studied. In article number 1902413, Won‐Sub Yoon and co‐workers propose the thermal expansion and oxygen vacancy as critical factors to affect the inherent thermal instability of Ni‐rich cathode materials. In the cover image, the thermal runaway of energy storage systems in industrial facilities is presented because it is closely related to the thermal instability of Ni‐rich cathode materials.